Aromatic dialdehyde-based bisbenzoxazines: The influence of relative position of oxazine rings. (22nd February 2021) - Tavernier, Romain; Granado, Lérys; Foyer, Gabriel; David, Ghislain; Caillol, Sylvain
Abstract: Polybenzoxazines are known to have superior thermal stability. Especially, the use of aromatic aldehydes instead of formaldehyde for the synthesis of benzoxazines monomers could improve this stability. However, the increase in aromatic content of the monomer can prevent the processability. The objective of this article is to understand the relationships between the conformation of an aromatic dialdehyde and its thermal properties. Two benzoxazine monomers were synthesized, based on salicylaldehyde, furfurylamine and respectively terephthalaldehyde (TPA, para configuration) and isophthalaldehyde (IPA, meta). Structural characterizations showed differences in intramolecular interactions between the two isomers. The melting transition of "meta" isomer was 50 °C lower than for "para" monomer, whereas polymerization temperatures and enthalpies were nearly the same. Volatile compounds released during the polymerization were the same in both cases, as investigated by mass spectrometry (Py-GC/MS). Curing kinetics using model-free kinetic methods revealed that the E-dependency follows the same trend for both monomers. Finally, thermal degradation monitored by thermogravimetric analysis under inert atmosphere was similar, with high degradation temperatures and high char yields (64%). Graphical abstract: Image 1 Highlights: 2-Substituted benzoxazines from aromatic dialdehydes isomers were synthesized. Isoconversional analysis was useful in the comparison of polymerization mechanisms. No difference between monomers was shown, except on the melting temperature. Process parameters can be controlled without affecting materials properties.